2017
DOI: 10.1371/journal.pone.0173034
|View full text |Cite
|
Sign up to set email alerts
|

Osteoprotegerin levels in ST-elevation myocardial infarction: Temporal profile and association with myocardial injury and left ventricular function

Abstract: BackgroundElevated levels of osteoprotegerin (OPG) have been associated with adverse outcomes in ST-elevation myocardial infarction (STEMI). However, the role of OPG in myocardial injury and adverse remodeling in STEMI patients remains unclear. The aims of this observational cohort study were to evaluate: 1) the temporal profile of OPG during STEMI, 2) possible associations between OPG measured acutely and after 4 months, with infarct size, adverse left ventricular (LV) remodeling, microvascular obstruction (M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 33 publications
(37 reference statements)
1
13
0
Order By: Relevance
“…In the present study, the results on CMR first-pass perfusion at rest showed no significant differences between patients treated with PCI with or without postconditioning, which is in accordance with the findings in the main study [ 19 , 29 ].…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, the results on CMR first-pass perfusion at rest showed no significant differences between patients treated with PCI with or without postconditioning, which is in accordance with the findings in the main study [ 19 , 29 ].…”
Section: Discussionsupporting
confidence: 93%
“…The anticoagulant heparin displays close structural relationship to HS [236], and is routinely administrated to patients prior to percutaneous coronary intervention (PCI) [237]. This drug has previously been shown to influence circulating levels of several cytokines [238,239]. To study whether heparin influenced the level of circulating legumain, a small population of patients (n=9) with suspected stable coronary artery disease was administrated with 5000 IU heparin.…”
Section: Importance Of Glycosylation For Cellular Localization Of Legmentioning
confidence: 99%
“…Previous clinical studies have shown that the elevation of both OPG and oxLDL plasma levels in patients with recent MI was associated with the severity of MI, with heart failure, and with long-term adverse outcomes. [ 23 , 25 ]. In accordance with our results, Shetelig C et al demonstrated that circulating OPG levels were increased in the acute phase of ST-elevation MI patients and were only slightly decreased after 4 months, suggesting that OPG levels may remain increased after acute and subacute MI.…”
Section: Discussionmentioning
confidence: 99%
“…In accordance with our results, Shetelig C et al demonstrated that circulating OPG levels were increased in the acute phase of ST-elevation MI patients and were only slightly decreased after 4 months, suggesting that OPG levels may remain increased after acute and subacute MI. [ 25 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation